The Role of Bequests in Shaping Wealth Inequality: Evidence from Danish Wealth Records - Boserup, Simon H.; Kopczuk, Wojciech; Kreiner, Claus T. (American Economic Review, 2016)
Using Danish administrative data, we estimate the impact of bequests on the level and inequality of wealth. We compare the distributions of wealth over time of people whose parent died and those whose parent did not. Bequests account for 26 percent of the average post-bequest wealth 1-3 years after parental death and significantly affect wealth throughout the distribution. Bequests increase absolute wealth inequality (variance of the distribution censored at the top/bottom 1% increases by 33 percent), but reduce relative inequality (the top 1% share declines by 6 percentage points from the base of 31 percent).